1978
DOI: 10.1111/1523-1747.ep12515092
|View full text |Cite
|
Sign up to set email alerts
|

Flare and Itch Induced by Substance P in Human Skin

Abstract: Intradermal injection of synthetic substance P (10(-7)--10(-5) M in humans produced flare, wheal and itching. These responses were inhibited by oral pretreatment of the subjects with an antihistaminic drug (chlorcyclizine) or by local pretreatment with Compound 48/80 administered to deplete the local stores of mast-cell bound histamine. The findings indicate that the responses induced by substance P were mainly mediated by histamine released from the dermal mast cells. In contrast to previously studied histami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
199
0
4

Year Published

1982
1982
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(222 citation statements)
references
References 22 publications
11
199
0
4
Order By: Relevance
“…Hypothetically, the SP-induced secretion may be secondary to mast cell degranulation (Hagermark et al, 1978) and subsequent histamine release (Konno & Togawa, 1979b). From experimental studies (Lundblad & Lundberg, 1984), it can be deduced that the mechanism underlying the secretory response to capsaicin may be: (1) a local axon reflex with the subsequent release of mediators from sensory nerves acting on the exocrine elements in the nasal mucosa, (2) a parasympathetic reflex relayed via axon collaterals of sensory nerves in the sphenopalatine ganglion, or (3) a centrally-mediated parasympathetic reflex (see Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothetically, the SP-induced secretion may be secondary to mast cell degranulation (Hagermark et al, 1978) and subsequent histamine release (Konno & Togawa, 1979b). From experimental studies (Lundblad & Lundberg, 1984), it can be deduced that the mechanism underlying the secretory response to capsaicin may be: (1) a local axon reflex with the subsequent release of mediators from sensory nerves acting on the exocrine elements in the nasal mucosa, (2) a parasympathetic reflex relayed via axon collaterals of sensory nerves in the sphenopalatine ganglion, or (3) a centrally-mediated parasympathetic reflex (see Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…The activities of substance P-related peptides as histamine releasers in rat mast cells is correlated with their activity in producing flare responses in human skin (Foreman & Jordan, 1981) and there is evidence that the flare response to intradermal injection of substance P is mediated by histamine release from skin mast cells (Hagermark et al, 1978;Foreman & Jordan, 1981). We have shown in this study that neurotensin produces flare, and also wheal responses, when injected intradermally into human skin, but it is less potent than substance P in these respects.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical and neurochemical evidence indicates that substance P is present in the peripheral as well as the central terminals of some primary afferent neurones (Hokfelt, Kellerth, Nilsson & Pemow, 1975; Cuello, Del Fiacco & Paxinos, 1978) and it is conceivable, therefore, that substance P is released from these neurones in the skin and other organs. It has been proposed that substance P, released from sensory nerve endings, plays a part in the triple response of skin to an injury (Hagermark et al, 1978;), and we have already pointed out that the flare, which is believed to be mediated by the so-called 'axon reflex' in the triple response, is induced only by those peptides which also release histamine from rat mast cells in vitro (Foreman & Jordan, 1981). The relationship between substance P and mast cells in injury and inflammation is thus of interest, and inhibitors of the peripheral actions of substance P might have a suppressant effect on some inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axon reflex flare (vasodilatation) follows intradermal injection of histamine (Lewis, 1927) and substance P (SP) (Hagermark, Hokfelt & Pernow, 1978) in human skin, and is inhibited by topical capsaicin pretreatment (Carpenter & Lynn, 1981;Bernstein, Swift, Soltani & Lorincz, 1981). It has been postulated that axon reflex flare is produced by release of SP from nociceptive sensory afferent terminals in the skin (Burnstock, 1977;Henry, 1977), and it has been demonstrated that SP is released from the central terminals of such nociceptive fibres (Nicoll, Schenker & Leeman, 1980).…”
Section: Introductionmentioning
confidence: 99%